Experimental Validation of Multi-Epitope Peptides Including Promising MHC Class I- and II-Restricted Epitopes of Four Known Leishmania infantum Proteins - Agallou, Maria; Athanasiou, Evita; Koutsoni, Olga; Dotsika, Eleni; Karagouni, Evdokia (Frontiers in Immunology, 2014)
Leishmaniasis is a significant worldwide health problem for which no vaccine exists. Activation of CD4+ and CD8+ T cells is crucial for the generation of protective immunity against parasite. Recent trend in vaccine design has been shifted to epitope-based vaccines that are more specific, safe, and easy to produce. In the present study, four known antigenic Leishmania (L.) infantum proteins, CPA, histone H1, KMP-11 and LeIF were analysed for the prediction of binding epitopes to H2d MHC class I and class II molecules, using online available algorithms. Based on in silico analysis, eight peptides including highly scored MHC class I- and class II-restricted epitopes were synthesized. Peptide immunogenicity was validated in MHC compatible BALB/c mice immunized with each synthetic peptide emulsified in CFA/IFA. CPA_p2, CPA_p3, H1_p1 and LeIF_p6 induced strong spleen cell proliferation upon in vitro peptide re-stimulation. In addition, the majority of the peptides, except of LeIF_p1 and KMP-11_p1, induced IFN-γ secretion, while KMP-11_p1 indicated a suppressive effect on IL-10 production. CPA_p2, CPA_p3, LeIF_p3 and LeIF_p6 induced IFN-γ-producing CD4+ T cells indicating a TH1 type response. In addition, CPA_p2, CPA_p3 and H1_p1 induced also the induction of CD8+ T cells. The induction of peptide-specific IgG in immunized mice designated also the existence of B cell epitopes in peptide sequences. Combining immunoinformatic tools and experimental validation, we demonstrated that CPA_p2, CPA_p3, H1_p1, H1_p3, CPA_p2, LeIF_p3 and LeIF_p6 are likely to include potential epitopes for the induction of protective cytotoxic and/or TH1-type immune responses supporting the feasibility of peptide-based vaccine development for leishmaniasis.